INTERVENSI PENDIDIKAN KESEHATAN KOMUNITAS MENGENAI TUBERCULOSIS PARU PADA PAGUYUBAN PARU DESA PLEREAN, SUMBERJAMBE, JEMBER - Kusuma, Irawan Fajar; Hartanti, Ragil Ismi (FKM - UNEJ, 2007)
Pulmonary TB is a chronic infectious disease and one of the most important health problems in the world, especially in developing countries such as Indonesia. Anti TB drugs resistance and how easy it spread because the lack of information and knowledge are the major constrains in TB eradication. Many efforts has been taken to Â overcome this problems, however, its incidence and prevalence is still high. Health community education, including the spreading of pulmonary TB and how to recognize the clinical manifestations, is one of the effort to overcome this problem. The aim of this study was to know the effect of health community education about pulmonary TB to Paguyuban Paru Group at Plerean, Subdistrict Sumber Jambe, Jember. This is a quasi experimental study, using pre test and post test after a health community education has been given. By paired sample test, the result showed significant difference (p<0,05) in the knowledge about pulmonary TB among the member of Paguyuban Paru at Plerean, Subdistrict Sumber Jambe, Jember, before and after health community education has been given. The conclusiÃ³n of this study is that health community education effectively increase the knowledge about pulmonary TB and, next, can compress the incidence of pulmonary TB in Indonesia Â Key words : pulmonary TB, community, health education